MEDIA DEVELOPMENT APEDU EDUCATIONAL APPLICATIONS BASED ON ANDROID IN FORCE MATERIAL - Dewi Rakhmawati (Renjana Pendidikan Dasar, 2022)
Learning media is one way to facilitate in conveying the content of material from educators to learners. In the era of technological development today there are new habits at the level of elementary school education, one of which is using digital media as a means to convey material. Therefore, there needs to be a learning media that is able to utilize technology, especially for elementary school. This research is included in research and development that later produces a teaching material in the form of learning media that utilizes based on android technology by using animation and backing sound features that are able to stimulate students' thinking systems. To obtain a research learning media also aims to know the process, implementation, feasibility, and effectiveness of the media. The research process is carried out using the ADDIE model which has five stages in the research. In the development stage researchers obtained a score from media experts, material experts, RPP experts, and design experts by 90%, while in the implementation stage researchers obtained a score of 79.15% which was obtained from the average score given by media users. Then for the eligibility score is taken at the stage of the media creation process to the expert validation stage, so as to obtain an average score of 90%. While the effectiveness of the learning media is taken from the results of the t test conducted after the use of learning media, obtained t count 7,970 and t table 2.144 so that Ho is rejected and Ha is accepted with a significance level of 0.00 with a correlation value of 0.872 which means there is a positive influence from the use of learning media. The score indicates that the media developed by researchers falls into a category that is validly feasible and effectively used by elementary school students